An Analysis Of Al-baya' Bithaman Ajil Contract In Islamic Financing Products: A Case Study In Brunei - Mohd Rizal Muwazir; Hajah Sabariah Haji Hassan; Noradilah Abdul Hadi; Sri Widyastuti; Mohammad Said (Hampstead Psychological Associates, 2024)
Indexed by Scopus/ERA